2020
DOI: 10.18357/bigr12202019589
|View full text |Cite
|
Sign up to set email alerts
|

Refugees and the Dublin Convention

Abstract: The Dublin Convention defines which EU State is responsible for the asylum application of third country nationals or stateless persons. According to this Convention, the first Member State in which an asylum seeker enters is responsible for the person’s asylum procedure. It thereby stands in gross contrast to the freedom of mobility of EU-citizens within Europe. While extensive research has focused on the attempts to build up a Common European Asylum System, mostly taking up an institutional perspective, only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…It led to a return of mental borders long thought forgotten and even overcome which were being drawn along national lines. This could already be observed during the migration crisis in 2015, when the massive inflow of refugees into the EU caused problems of migrant integration and new waves of nationalism and xenophobia, also in France and in Germany (Bartel, Delcroix, & Pape 2020;Beaupré & Fischer 2020).…”
Section: Late May To Mid-june: the De-confinementmentioning
confidence: 96%
“…It led to a return of mental borders long thought forgotten and even overcome which were being drawn along national lines. This could already be observed during the migration crisis in 2015, when the massive inflow of refugees into the EU caused problems of migrant integration and new waves of nationalism and xenophobia, also in France and in Germany (Bartel, Delcroix, & Pape 2020;Beaupré & Fischer 2020).…”
Section: Late May To Mid-june: the De-confinementmentioning
confidence: 96%
“…The pandemic showed that Europe was not immune to this phenomenon. As the last decade has shown signs of a hardening of European borders especially in the context of the wave of terrorist attacks that flared up across Europe-especially in France in 2015-2016-and of the so-called migrant "crisis" that started in 2015 (Bartel, Delcroix, and Pape 2020;UNHCR 2020;Wassenberg 2020), this trend of chronic reinforcements of borders within the Schengen Area has persisted and expanded. The COVID-19 pandemic temporarily put on hold the Schengen Area insofar as all countries closed their borders.…”
Section: Lockdown Complicates Lives Of Border Residentsmentioning
confidence: 99%